2020
DOI: 10.1101/2020.09.23.309591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rad21l1 cohesin subunit is dispensable for spermatogenesis but not oogenesis in zebrafish

Abstract: Meiosis produces haploid gametes that will give rise to the next diploid generation. Chromosome segregation errors occurring at one or both meiotic divisions result in aneuploidy, which can lead to miscarriages or birth defects in humans. During meiosis I, ring-shaped cohesin complexes play important roles to aid in the proper segregation of homologous chromosomes. While REC8 is a specialized meiosis-specific cohesin that functions to hold sister chromatids together, the role of its vertebrate-specific paralog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Zebrafish mutants disrupting genes encoding synaptonemal complex proteins sycp1 , sycp2 , and sycp3 as well as the meiotic cohesion component smc1b , developed as 100% sterile males due to failures in meiotic prophase I (7375,78). Mutations that specifically effect female meiosis, such as mutations in zar1 and rad21l1 , failed to develop as female or were male biased, respectively (54,76). In these mutants, males were normal indicating a requirement in female meiosis but not spermatogenesis (54,76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish mutants disrupting genes encoding synaptonemal complex proteins sycp1 , sycp2 , and sycp3 as well as the meiotic cohesion component smc1b , developed as 100% sterile males due to failures in meiotic prophase I (7375,78). Mutations that specifically effect female meiosis, such as mutations in zar1 and rad21l1 , failed to develop as female or were male biased, respectively (54,76). In these mutants, males were normal indicating a requirement in female meiosis but not spermatogenesis (54,76).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that specifically effect female meiosis, such as mutations in zar1 and rad21l1 , failed to develop as female or were male biased, respectively (54,76). In these mutants, males were normal indicating a requirement in female meiosis but not spermatogenesis (54,76). We demonstrated that adad1 mutant spermatocytes failed to progress beyond the zygotene stage and that ovarian follicles were never formed in the bipotential gonad stage.…”
Section: Discussionmentioning
confidence: 99%
“…Images of eggs and embryos were acquired using a dissecting microscope. All data and related metadata underlying the findings have been deposited and are available at DRYAD (doi: 10.25338/B8V91Q) [81].…”
Section: Imagingmentioning
confidence: 99%
“…Testis-specific H1 histone (H1t) 0.714 Associated with repressed chromatin domains in pachytene spermatocytes (Mahadevan et al, 2020) Mediator of DNA damage checkpoint protein 1 (MDC1) 0.697 Functions in chromosome-wide silencing of the sex body (Ichijima et al, 2011) TP53-binding protein 1 (53BP1) 0.624 DDR protein and localizes to the sex body (Lu et al, 2013) Histone-lysine N-methyltransferase SETDB1 0.338 Links meiotic DDR to sex chromosome silencing (Hirota et al, 2018) Pachytene checkpoint protein 2 homolog (Trip13) 0.338 Required for recombination and meiotic chromosome structure (Roig et al, 2010) Synaptonemal complex protein 3 (SYCP3) 0.256 Component of synaptonemal complex (Syrjänen et al, 2014) Cohesin subunit SA-3 (STAG3) 0.173 Maintaining centromere chromatid cohesion; required for DSB repair and synapsis (Hopkins et al, 2014) DNA mismatch repair protein Mlh1 0.146 Homologous recombination and DSB repair (Cannavo et al, 2020) Synaptonemal complex protein 2 (SYCP2) 0.144 Component of synaptonemal complex (Feng et al, 2017) Serine/threonine-protein kinase Chk1 0.137 DNA damage response (Nie et al, 2017) Meiotic recombination protein REC8 0.124 Sister-chromatid cohesion and crossover recombination (Yoon et al, 2016) HORMA domain-containing protein 1 (HORMAD1) 0.094 Synaptonemal complex formation, recombination and chromosome segregation (Shin et al, 2010) Double-strand-break repair protein rad21-like protein 1 (Rad21L1) 0.038 Maintaining the integrity of meiotic chromatin architecture (Blokhina et al, 2020) Synaptonemal complex protein 1 (SYCP1) 0.036 Component of synaptonemal complex (de Vries et al, 2005) Serine-protein kinase ATM 0.026 Controlling DSB formation and recombination (Lange et al, 2011;Kurzbauer et al, 2021) and exert specific biological functions (Mackenzie et al, 2017).…”
Section: Protein Name Idr Content Functionsmentioning
confidence: 99%